2017
DOI: 10.4028/www.scientific.net/nhc.13.149
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Biodrugs with Nanoparticles of Ferrum, Cobalt and Cuprum on Growth, Development, Yield and Phytohormone Status of Fodder and Red Beets

Abstract: The article presents the influence of biopreparations containing nanoparticles of ferrum, cobalt and cuprum on fodder and red beets. We have investigated parameters of plants growth and development, the phytohormonic status of vegetating plants, the yield, its structure and chemical composition of fodder and red beets including vitamin C and carotene. We have proved ecological safety of nanopreparations on the basis of experiment area soil chemical composition. We have tried nanobiopraparations in the technolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…The application of NPs increases the synthesis of indole acetic acid (IAA) and gibberellins (GA), which in turn improve plant growth under DS ( Churilova et al., 2017 ; Li et al., 2021 ). The application of Fe-NPs greatly enhanced the growth and yield of strawberry ( Fragaria × ananassa Duch.)…”
Section: Nanoparticles Improve Osmolyte Accumulation and Maintain Hor...mentioning
confidence: 99%
“…The application of NPs increases the synthesis of indole acetic acid (IAA) and gibberellins (GA), which in turn improve plant growth under DS ( Churilova et al., 2017 ; Li et al., 2021 ). The application of Fe-NPs greatly enhanced the growth and yield of strawberry ( Fragaria × ananassa Duch.)…”
Section: Nanoparticles Improve Osmolyte Accumulation and Maintain Hor...mentioning
confidence: 99%
“…Copper and cobalt are the microelements essential for plant growth [37]. Recently, copper and cobalt oxide NP powders have been synthesized [38,39]. However, the fate of these NPs and their impact on consumers remain to be investigated.…”
Section: Metal Oxide Nanoparticles: a General Overviewmentioning
confidence: 99%
“…One of the most important elements of intensive resource-saving wheat production technology is pre-sowing seed treatment. Studies have shown that together with dressing agents against diseases and pests, it is effective to use growth stimulants [4], but the greatest effect was observed from the use of suspensions of metal-microelement nanopowders [5][6].…”
Section: Introductionmentioning
confidence: 99%